Hubungan Anatar pengetahuan dan Sikap Ibu Terhadap Pemilihan Metode Alat Kontrasepsi Dalam Rahim Di Puskesmas Kayamanya Tahun 2019 - Hatijar Hatijar; Irma Suryani Saleh (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
One of the rational contraceptives is intrauterine contraception. Contraceptives that have high reversibility and effectiveness are 0.6–0.8 / 100 family planning acceptors. Descriptive research with a cross-sectional approach. The sampling technique used was total sampling with a sample of 94 KB acceptors. The population in this study were all mothers who used family planning acceptors. There is a relationship between knowledge and the choice of contraceptive use with p-value = 0.000, while the relationship between attitudes and the choice of IUD contraceptive method is p = 0.001 That there is a relationship between knowledge and attitudes of mothers towards the choice of intrauterine contraceptive method